Generating correct compositions of semantic web services with respect to temporal constraints - Machado, Efraim Zalmoxis de Almeida; Claro, Daniela Barreiro; Andrade, Aline Maria Santos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Services are being widely published over the Web and many services may be composed to attend a user's need. A composition of services can demand complex requirements to get an executable composition. Temporal restrictions are one of these requirements. As compositions are dynamically composed, model checking can be applied to verify if compositions are correct in relation to the temporal restrictions required. In this work we propose an algorithm that creates semantic web service compositions and verifies the correctness of a composition checking the temporal restrictions of each iteration. Experiments were carried out and the precision of retrieved services and their execution time were analyzed.